SISTEM INFORMASI PADA MTS DARUL DA'WAH WAL IRSYAD KOTA HARAPAN KEC. MUARA SABAK TIMUR BERBASIS WEB: Information System;MTs;Visual Studio Code;MYSql;Website. - Suana, Irma; Sulaiman (FORTECH (Journal of Information Technology), 2021)
Along with the development of information technology makes the computer at this time as a tool to obtain information. Therefore, with the development of this technological advancement, MTs DDI Kota Harapan needs to promote itself through an online website on the internet. research with the title "INFORMATION SYSTEM AT MTS DARUL DA'WAH WAL IRSYAD KOTA HARAPAN KEC. MUARA SABAK TIMUR WEB-BASED". formulation of the problem "How to design a web-based school information system at MTs DDI Kota Harapan using the PHP and MYSQL programming languages". The purpose of this study is to produce a school website information system design at MTs DDI Kota Harapan, to design a school information system that can be accessed easily without being limited by time and distance. This study uses a descriptive analysis approach. The data collection techniques used are observation and interviews. The research approach used is descriptive analysis approach. The theoretical basis used is secondary data, namely data that has been collected. The results of this study are the design of this website using the PHP programming language, MYSql database, CodeIgniter Framework and using Visual Studio Code and Wamp Server tools, this web-based information system is an information medium for MTs Darul Da'wah Wal Irsyad Kota Harapan.